2015
DOI: 10.1186/s13039-015-0207-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of small segmental translocations in patients with repeated implantation failure and recurrent miscarriage using next generation sequencing after in vitro fertilization/intracytoplasmic sperm injection

Abstract: BackgroundTo develop a novel preimplantation genetic screening (PGS) test using next generation sequencing(NGS) as a alternative to current array comparative genomic hybridization (array CGH) method for detection of small segmental translocations in two patients with repeated implantation failure (RIF) and recurrent miscarriage (RM). Inconsistent results were resolved by validation with fluorescence in situ hybridization (FISH).Case PresentationOne couple with normal cytogenetic and array CGH result suffered f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…As sequencing costs decrease further, allowing for a greater read depth per sample for the same or a reduced price, NGS approaches provide simultaneous evaluation of single-gene disorders and translocations with comprehensive aneuploidy screening from the same biopsy without the requirement for multiple technological platforms (7,18,30,31). Compared to array CGH or SNP array, the NGS approach not only detects mosaic blastocysts, but may also be effective in characterizing small abnormal chromosomal fragments (24). In the present study, NGS-based 24-aneuploidy screening revealed that embryo 2 was mosaic; the method allows for accurate detection of segmental imbalances as small as ~4 Mb in size due to the high resolution.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…As sequencing costs decrease further, allowing for a greater read depth per sample for the same or a reduced price, NGS approaches provide simultaneous evaluation of single-gene disorders and translocations with comprehensive aneuploidy screening from the same biopsy without the requirement for multiple technological platforms (7,18,30,31). Compared to array CGH or SNP array, the NGS approach not only detects mosaic blastocysts, but may also be effective in characterizing small abnormal chromosomal fragments (24). In the present study, NGS-based 24-aneuploidy screening revealed that embryo 2 was mosaic; the method allows for accurate detection of segmental imbalances as small as ~4 Mb in size due to the high resolution.…”
Section: Discussionmentioning
confidence: 68%
“…The template positive Ion Sphere Particles were sequenced on an Ion Torrent Personal Genome Machine (PGM) (Life Technologies Ltd.) according to the instructions of the Ion Sequencing kit v2.0 (Thermo Fisher Scientific, Inc.�. The remaining WGA products were simultaneously subjected to aneuploidy screening by NGS according to a standard protocol using the Ion Torrent System (Thermo Fisher Scientific, Inc.� as previously described (24). The data from the PGM sequencing were analyzed by Peking Jabrehoo Med Tech., Ltd. (Beijing, China).…”
Section: Introductionmentioning
confidence: 99%
“…A larger patient population would increase the power of the study to detect other embryo morphological characteristics limiting implantation of a euploid embryo. Further limitations to our study relate to the fact that now most IVF units perform blastocyst biopsy as standard approach to PGS, and the ploidy status of the embryos is increasingly being assessed by NGS . However, as the field of reproductive medicine is continually evolving, it is important to critically evaluate all techniques before embracing new technologies and techniques.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the embryo is predisposed to aneuploidy, the most important factor limiting implantation, it is important to ensure the embryo for transfer is euploid. Pre‐implantation genetic screening (PGS) using array comparative genomic hybridisation (CGH) to determine embryo ploidy status is frequently employed, although being gradually superseded by next generation sequencing (NGS), which has a greater degree of resolution to detect abnormalities . As PGS excludes the majority of chromosomal abnormalities, it is a valuable tool to study the influence of several other co‐existing variables within the patient, the embryo or laboratory techniques employed, on the chance of a successful pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…The transfer of embryos without chromosome abnormalities by means of PGS, would improve the reproductive performance of couples with RM due to karyotyping abnormalities. Furthermore, PGS also being increasingly used for patients with a history of RM, even in the absence of parental translocations [38,39] …”
Section: Managementmentioning
confidence: 99%